2012
DOI: 10.1159/000338152
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Soluble Total and Hyperphosphorylated Tau Result in Early Behavioral Deficits and Distinct Changes in Brain Pathology in a New Tau Transgenic Mouse Model

Abstract: Tauopathies, characterized by hyperphosphorylation and aggregation of tau protein, include frontotemporal dementias and Alzheimer's disease. To explore disease mechanisms and investigate potential treatments, we generated a transgenic (tg) mouse line overexpressing human tau441 with V337M and R406W mutations. Biochemical characterization of these TMHT (Thy-1 mutated human tau) mice showed a significant increase in human transgene expression relative to endogenous murine tau by Western blot and multi-array immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…The parental single Tau mutant tg mice that we use have been reported to display moderate alterations in tau accumulation [27], additionally, previous studies have shown that adding GSK3β enhances the pathology [28], therefore Tau/GSK3β bigenic mice were generated by crossing Tau tg mice expressing human Tau under the mThy-1 promoter with GSK3β tg mice in order to enhance tau phosphorylation. These double tg mice were subsequently used to evaluate the effects of CBL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parental single Tau mutant tg mice that we use have been reported to display moderate alterations in tau accumulation [27], additionally, previous studies have shown that adding GSK3β enhances the pathology [28], therefore Tau/GSK3β bigenic mice were generated by crossing Tau tg mice expressing human Tau under the mThy-1 promoter with GSK3β tg mice in order to enhance tau phosphorylation. These double tg mice were subsequently used to evaluate the effects of CBL.…”
Section: Resultsmentioning
confidence: 99%
“…The mThy1-Tau (V337M and R406W) tg model has been shown to accumulate soluble p-Tau in the limbic system and to display spatial learning impairments [27]. The FTDP-17 R406W tau mutation has been described in an American, a Dutch, and a Japanese family [3032].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a Total cell number; b number of neurons; c number of non-neuronal cells; d Mass. The lines in d represent significant negative correlations of cerebellar mass with age for men (blue), and women (red) memory deficits of aging, now attributed to the subcellular, molecular action of b-amyloid oligomers on dendrites (Cochran et al 2014) and synapses (Ferreira and Klein 2011), and of hyperphosphorilation of tau-protein on neuronal physiology (Flunkert et al 2013). Further reduction leads to the involvement of genes and epigenetic control (Sebolella et al 2012;Piaceri et al 2015).…”
Section: On Quantitative Cellularity Studies and The Different Levelsmentioning
confidence: 99%
“…Thus, excessive Tau phosphorylation alone may be necessary and sufficient for pathological impairment of neural function. Although some studies in Tau mutant mice indeed correlate the onset of behavioural deficits [19,20] as well as disruptions in critical cellular signalling pathways [21] with soluble phospho-Tau levels in the absence of an elevation of insoluble Tau levels, such a demonstration without the confounding influences of FTD mutations and/or gross Tau overexpression remains elusive. Equally, the demonstration of improved memory upon the suppression of FTD Tau expression, despite continued formation/persistence of NFTs [22,23] further supports the notion that soluble Tau phosphorylation is strongly connected with neuronal dysfunction.…”
mentioning
confidence: 99%